Lysanda paste: a new option for root-end filling - Norberti Bernardineli; Clovis Monteiro Bramante; Ivaldo Gomes de Moraes; Roberto Brandão Garcia (University of São Paulo, 2007)
This study aimed to compare the apical sealing of root-end fillings performed with Lysanda (zinc oxide-eugenol paste) with radiopacifiers (iodoform or zinc oxide) and calcium hydroxide. Root-end cavities were prepared and filled with different materials, as follows: Group I - Lysanda paste with iodoform; Group II - Lysanda paste with iodoform and calcium hydroxide; Group III - Lysanda paste with iodoform and zinc oxide; Group IV - Lysanda paste with zinc oxide; Group V - mineral trioxide aggregate (MTA). After filling, the teeth were immersed in 2% methylene blue for analysis of marginal leakage. It was observed that marginal leakage occurred in all groups. Lysanda paste with iodoform showed the lowest leakage, with no statistically significant difference compared to the other groups. All materials can be considered as good options for root-end filling.